Acceleration of petaelectronvolt protons in the Galactic Centre - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, M.; Balzer, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; Bernhard, S.; Bernloehr, K.; et al. (Nature, 2016)
Galactic cosmic rays reach energies of at least a few petaelectronvolts(1) (of the order of 1015 electronvolts). This implies that our Galaxy contains petaelectronvolt accelerators ('PeVatrons'), but all proposed models of Galactic cosmic-ray accelerators encounter difficulties at exactly these energies(2). Dozens of Galactic accelerators capable of accelerating particles to energies of tens of teraelectronvolts (of the order of 10(13) electronvolts) were inferred from recent gamma-ray observations(3). However, none of the currently known accelerators-not even the handful of shell-type supernova remnants commonly believed to supply most Galactic cosmic rays-has shown the characteristic tracers of petaelectronvolt particles, namely, power-law spectra of.-rays extending without a cut-off or a spectral break to tens of teraelectronvolts(4). Here we report deep.-ray observations with arcminute angular resolution of the region surrounding the Galactic Centre, which show the expected tracer of the presence of petaelectronvolt protons within the central 10 parsecs of the Galaxy. We propose that the supermassive black hole Sagittarius A* is linked to this PeVatron. Sagittarius A* went through active phases in the past, as demonstrated by X-ray outbursts(5) and an outflow from the Galactic Centre(6). Although its current rate of particle acceleration is not sufficient to provide a substantial contribution to Galactic cosmic rays, Sagittarius A* could have plausibly been more active over the last 10(6)-10(7) years, and therefore should be considered as a viable alternative to supernova remnants as a source of petaelectronvolt Galactic cosmic rays.

A new SNR with TeV shell-type morphology: HESS J1731-347 - Abramowski, A.; Acero, Fabio; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2011)
Aims. The recent discovery of the radio shell-type supernova remnant (SNR), G353.6-0.7, in spatial coincidence with the unidentified TeV source HESS J1731-347 has motivated further observations of the source with the High Energy Stereoscopic System (HESS) Cherenkov telescope array to test a possible association of the γ-ray emission with the SNR. Methods. With a total of 59 h of observation, representing about four times the initial exposure available in the discovery paper of HESS J1731-347, the γ-ray morphology is investigated and compared with the radio morphology. An estimate of the distance is derived by comparing the interstellar absorption derived from X-rays and the one obtained from CO and HI observations. Results. The deeper γ-ray observation of the source has revealed a large shell-type structure with similar position and extension (r ∼ 0.25°) as the radio SNR, thus confirming their association. By accounting for the HESS angular resolution and projection effects within a simple shell model, the radial profile is compatible with a thin, spatially unresolved, rim. Together with RX J1713.7-3946, RX J0852.0-4622 and SN 1006, HESS J1731-347 is now the fourth SNR with a significant shell morphology at TeV energies. The derived lower limit on the distance of the SNR of 3.2 kpc is used together with radio and X-ray data to discuss the possible origin of the γ-ray emission, either via inverse Compton scattering of electrons or the decay of neutral pions resulting from proton-proton interaction. © 2011 ESO.
Keywords: Astroparticle physics; Cosmic rays; ISM: supernova remnants

Constraints on an annihilation signal from a core of constant dark matter density around the milky way center with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Physical Review Letters, 2015)

Constraints on axionlike particles with H.E.S.S. from the irregularity of the PKS 2155-304 energy spectrum - Abramowski, A.; Acero, F.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2013)
Axionlike particles (ALPs) are hypothetical light (sub-eV) bosons predicted in some extensions of the Standard Model of particle physics. In astrophysical environments comprising high-energy gamma rays and turbulent magnetic fields, the existence of ALPs can modify the energy spectrum of the gamma rays for a sufficiently large coupling between ALPs and photons. This modification would take the form of an irregular behavior of the energy spectrum in a limited energy range. Data from the H.E.S.S. observations of the distant BL Lac object PKS 2155-304 (z=0.116) are used to derive upper limits at the 95% C.L. on the strength of the ALP coupling to photons, g<2. 1×1011 GeV1 for an ALP mass between 15 and 60 neV. The results depend on assumptions on the magnetic field around the source, which are chosen conservatively. The derived constraints apply to both light pseudoscalar and scalar bosons that couple to the electromagnetic field. © 2013 American Physical Society.

Constraints on the gamma-ray emission from the cluster-scale AGN outburst in the Hydra A galaxy cluster - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
Context. In some galaxy clusters, powerful active galactic nuclei (AGN) have blown bubbles with cluster scale extent into the ambient medium. The main pressure support of these bubbles is not known to date, but cosmic rays are a viable possibility. For such a scenario copious gamma-ray emission is expected as a tracer of cosmic rays from these systems. Aims. Hydra A, the closest galaxy cluster hosting a cluster scale AGN outburst, located at a redshift of 0.0538, is investigated for being a gamma-ray emitter with the High Energy Stereoscopic System (H.E.S.S.) array and the Fermi Large Area Telescope (Fermi-LAT). Methods. Data obtained in 20.2 h of dedicated H.E.S.S. observations and 38 months of Fermi-LAT data, gathered by its usual all-sky scanning mode, have been analyzed to search for a gamma-ray signal. Results. No signal has been found in either data set. Upper limits on the gamma-ray flux are derived and are compared to models. These are the first limits on gamma-ray emission ever presented for galaxy clusters hosting cluster scale AGN outbursts. Conclusions. The non-detection of Hydra A in gamma-rays has important implications on the particle populations and physical conditions inside the bubbles in this system. For the case of bubbles mainly supported by hadronic cosmic rays, the most favorable scenario, which involves full mixing between cosmic rays and embedding medium, can be excluded. However, hadronic cosmic rays still remain a viable pressure support agent to sustain the bubbles against the thermal pressure of the ambient medium. The largest population of highly-energetic electrons, which are relevant for inverse-Compton gamma-ray production is found in the youngest inner lobes of Hydra A. The limit on the inverse-Compton gamma-ray flux excludes a magnetic field below half of the equipartition value of 16 μG in the inner lobes. © 2012 ESO.
Keywords: Galaxies: active; Galaxies: clusters: individual: Hydra A; Gamma rays: galaxies: clusters

Detailed spectral and morphological analysis of the shell type SNR RCW 86 - Abramowski, A.; Aharonian, F.; Ait Benkhali, F.; Akhperjanian, A. G.; Angüner, E. O.; Backes, M.; Balzer, A.; Becherini, Y.; Becker Tjus, J.; Berge, D.; Bernhard, S.; Bernlöhr, K.; et al. (Astronomy & Astrophysics, 2018)
Aims. We aim for an understanding of the morphological and spectral properties of the supernova remnant RCW 86 and for insights into the production mechanism leading to the RCW 86 very high-energy gamma-ray emission.Methods. We analyzed High Energy Spectroscopic System (H.E.S.S.) data that had increased sensitivity compared to the observations presented in the RCW 86 H.E.S.S. discovery publication. Studies of the morphological correlation between the 0.5-1 keV X-ray band, the 2-5 keV X-ray band, radio, and gamma-ray emissions have been performed as well as broadband modeling of the spectral energy distribution with two different emission models.Results. We present the first conclusive evidence that the TeV gamma-ray emission region is shell-like based on our morphological studies. The comparison with 2-5 keV X-ray data reveals a correlation with the 0.4-50 TeV gamma-ray emission. The spectrum of RCW 86 is best described by a power law with an exponential cutoff at E-cut = (3.5 +/- 1.2(stat)) TeV and a spectral index of Gamma approximate to 1.6 +/- 0.2. A static leptonic one-zone model adequately describes the measured spectral energy distribution of RCW 86, with the resultant total kinetic energy of the electrons above 1 GeV being equivalent to similar to 0.1% of the initial kinetic energy of a Type Ia supernova explosion (10(51) erg). When using a hadronic model, a magnetic field of B approximate to 100 mu G is needed to represent the measured data. Although this is comparable to formerly published estimates, a standard E-2 spectrum for the proton distribution cannot describe the gamma-ray data. Instead, a spectral index of Gamma(p) approximate to 1.7 would be required, which implies that similar to 7 x 10(49)/n(cm-3) erg has been transferred into high-energy protons with the effective density n(cm-3) = n/1 cm(-3). This is about 10% of the kinetic energy of a typical Type Ia supernova under the assumption of a density of 1 cm(-3).
Keywords: astroparticle physics; gamma rays: general; ISM: supernova remnants; cosmic rays

Diffuse Galactic gamma-ray emission with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2014)
Diffuse γ-ray emission is the most prominent observable signature of celestial cosmic-ray interactions at high energies. While already being investigated at GeV energies over several decades, assessments of diffuse γ-ray emission at TeV energies remain sparse. After completion of the systematic survey of the inner Galaxy, the H.E.S.S. experiment is in a prime position to observe large-scale diffuse emission at TeV energies. Data of the H.E.S.S. Galactic Plane Survey are investigated in regions off known γ-ray sources. Corresponding γ-ray flux measurements were made over an extensive grid of celestial locations. Longitudinal and latitudinal profiles of the observed γ-ray fluxes show characteristic excess emission not attributable to known γ-ray sources. For the first time large-scale γ-ray emission along the Galactic plane using imaging atmospheric Cherenkov telescopes has been observed. While the background subtraction technique limits the ability to recover modest variation on the scale of the H.E.S.S. field of view or larger, which is characteristic of the inverse Compton scatter-induced Galactic diffuse emission, contributions of neutral pion decay as well as emission from unresolved γ-ray sources can be recovered in the observed signal to a large fraction. Calculations show that the minimum γ-ray emission from π0 decay represents a significant contribution to the total signal. This detection is interpreted as a mix of diffuse Galactic γ-ray emission and unresolved sources.

Discovery of gamma-ray emission from the extragalactic pulsar wind nebula N 157B with H.E.S.S. - Abramowski, A.; Acero, Fabio; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
We present the significant detection of the first extragalactic pulsar wind nebula (PWN) detected in gamma rays, N- 157B, located in the large Magellanic Cloud (LMC). Pulsars with high spin-down luminosity are found to power energised nebulae that emit gamma rays up to energies of several tens of TeV. N- 157B is associated with PSR- J0537-6910, which is the pulsar with the highest known spin-down luminosity. The High Energy Stereoscopic System telescope array observed this nebula on a yearly basis from 2004 to 2009 with a dead-time corrected exposure of 46- h. The gamma-ray spectrum between 600- GeV and 12- TeV is well-described by a pure power-law with a photon index of 2.8 ± 0.2 ± 0.3 and a normalisation at 1- TeV of (8.2 ± 0.8 ± 2.5 ) × 10 cm - s - TeV . A leptonic multi-wavelength model shows that an energy of about 4 × 10 erg is stored in electrons and positrons. The apparent efficiency, which is the ratio of the TeV gamma-ray luminosity to the pulsar's spin-down luminosity, 0.08% ± 0.01%, is comparable to those of PWNe found in the Milky Way. The detection of a PWN at such a large distance is possible due to the pulsar's favourable spin-down luminosity and a bright infrared photon-field serving as an inverse-Compton-scattering target for accelerated leptons. By applying a calorimetric technique to these observations, the pulsar's birth period is estimated to be shorter than 10 ms. © ESO, 201
Keywords: Gamma rays: general; ISM: supernova remnants; Magellanic Clouds; Pulsars: individual: PSR J0537-6910

Discovery of high and very high-energy emission from the BL Lacertae object SHBL J001355.9-185406 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy and Astrophysics, 2013)
Keywords: BL Lacertae objects: individual: SHBL J001355.9-185406; gamma rays: general

Discovery of TeV γ-ray emission from PKS 0447-439 and derivation of an upper limit on its redshift - Abramowski, A.; Acero, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Behera, B.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Very high-energy γ-ray emission from PKS 0447-439 was detected with the H.E.S.S. Cherenkov telescope array in December 2009. This blazar is one of the brightest extragalactic objects in the Fermi bright source list and has a hard spectrum in the MeV to GeV range. In the TeV range, a photon index of 3.89 ± 0.37 (stat) ±0.22 (sys) and a flux normalisation at 1 TeV, Φ = (3.5 ± 1.1(stat) ± 0.9(sys)) × 10 cm s TeV were found. The detection with H.E.S.S. triggered observations in the X-ray band with the Swift and RXTE telescopes. Simultaneous UV and optical data from Swift UVOT and data from the optical telescopes ATOM and ROTSE are also available. The spectrum and light curve measured with H.E.S.S. are presented and compared to the multi-wavelength data at lower energies. A rapid flare is seen in the Swift XRT and RXTE data, together with a flux variation in the UV band, at a time scale of the order of one day. A firm upper limit of z < 0.59 on the redshift of PKS 0447-439 is derived from the combined Fermi-LAT and H.E.S.S. data, given the assumptions that there is no upturn in the intrinsic spectrum above the Fermi-LAT energy range and that absorption on the extragalactic background light (EBL) is not weaker than the lower limit provided by current models. The spectral energy distribution is well described by a simple one-zone synchrotron self-Compton scenario, if the redshift of the source is less than z â‰ 0.4. © 2013 ESO.
Keywords: BL Lacertae objects: individual: PKS 0447-439; Galaxies: active; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Discovery of the Hard Spectrum VHE γ-Ray Source HESS J1641-463 - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Uner, E. O. Ang; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astrophysical Journal Letters, 2014)
Keywords: cosmic rays; gamma rays: general; ISM: individual objects (SNR G338.30.0; SNR G338.5+0.1)

Discovery of the source HESS J1356-645 associated with the young and energetic PSR J1357-6429 - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; et al. (Astronomy & Astrophysics, 2011)
Context. Several newly discovered very-high-energy (VHE; E > 100 GeV) γ-ray sources in the Galaxy are thought to be associated with energetic pulsars. Among them, middle-aged (10 yr) systems exhibit large centre-filled VHE nebulae, offset from the pulsar position, which result from the complex relationship between the pulsar wind and the surrounding medium, and reflect the past evolution of the pulsar. Aims. Imaging Atmospheric Cherenkov Telescopes (IACTs) have been successful in revealing extended emission from these sources in the VHE regime. Together with radio and X-ray observations, this observational window allows one to probe the energetics and magnetic field inside these large-scale nebulae. Methods. H.E.S.S., with its large field of view, angular resolution of 0.1° and unprecedented sensitivity, has been used to discover a large population of such VHE sources. In this paper, the H.E.S.S. data from the continuation of the Galactic Plane Survey (-80° < < 60°, |b| < 3°), together with the existing multi-wavelength observations, are used. Results. A new VHE γ-ray source was discovered at RA (J2000) = 135600, Dec (J2000) =-64°30′00′′ with a 2′ statistical error in each coordinate, namely HESS J1356-645. The source is extended, with an intrinsic Gaussian width of (0.20 ± 0.02)°. Its integrated energy flux between 1 and 10 TeV of 8 × 10 erg cm s represents ∼11% of the Crab Nebula flux in the same energy band. The energy spectrum between 1 and 20 TeV is well described by a power law dN/dE E with photon index Γ = 2.2 ± 0.2 ± 0.2. The inspection of archival radio images at three frequencies and the analysis of X-ray data from ROSAT/PSPC and XMM-Newton/MOS reveal the presence of faint non-thermal diffuse emission coincident with HESS J1356-645. Conclusions. HESS J1356-645 is most likely associated with the young and energetic pulsar PSR J1357-6429 (d = 2.4 kpc, τ = 7.3 kyr and Å-= 3.1 × 10 erg s), located at a projected distance of ∼5 pc from the centroid of the VHE emission. HESS J1356-645 and its radio and X-ray counterparts would thus represent the nebula resulting from the past history of the PSR J1357-6429 wind. In a simple one-zone model, © 2011 ESO.
Keywords: gamma rays: general; ISM: individual objects: HESS J1356-645; ISM: individual objects: PSR J1357-6429; surveys

Discovery of the VHE gamma-ray source HESS J1832-093 in the vicinity of SNR G22.7-0.2 - Abramowski, A.; Acero, F.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguner, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
Keywords: astroparticle physics; ISM: individual objects: HESS J1832-093; ISM: individual objects: SNR G22.7-0.2; gamma-rays: general

Discovery of variable VHE gamma-ray emission from the binary system 1FGL J1018.6-5856 - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balzer, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; Bernhard, S.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2015)
Re-observations with the HESS telescope array of the very high-energy (VHE) source HESS J1018-589A that is coincident with the Fermi-LAT gamma-ray binary 1FGL J1018.6-5856 have resulted in a source detection significance of more than 9 sigma and the detection of variability (chi(2)/nu of 238.3/155) in the emitted gamma-ray flux. This variability confirms the association of HESS J1018-589A with the high-energy gamma-ray binary detected Fermi-LAT and also confirms the point-like source as a new VHE binary system. The spectrum of HESS J1018-589A is best fit with a power-law function with photon index Gamma = 2.20 +/- 0.14(stat) +/- 0.2(sys). Emission is detected up to similar to 20 TeV. The mean differential flux level is (2.9 +/- 0.4) x 10(-13) TeV-1 cm(-2) s(-1) at 1 TeV, equivalent to similar to 1% of the flux from the Crab Nebula at the same energy. Variability is clearly detected the night-by-night light curve. When folded on the orbital period of 16.58 days, the rebinned light curve peaks in phase with the observed X-ray high-energy phaseograms. The fit of the HESS phaseogram to a constant flux provides evidence of periodicity at the level of N-sigma > 3 sigma. The of the VHE phaseogram and measured spectrum suggest a low-inclination, low-eccentricity system with a modest impact from VHE gamma-ray due to pair production (tau less than or similar to 1 at 300 GeV).
Keywords: Acceleration of particles; Gamma rays: stars; Radiation mechanisms: non-thermal; Stars: individual: 1FGL J1018.6-5856; X-rays: binaries

Discovery of very high energy γ-ray emission from the BL Lacertae object PKS 0301-243 with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2013)
The active galactic nucleus PKS 0301-243 (z = 0.266) is a high-synchrotron-peaked BL Lac object that is detected at high energies (HE, 100 MeV <e 0301-243="" 100="" at="" by="" discovery="" e="" energies="" fermi="" high="" lat.="" of="" on="" paper="" pks="" reports="" the="" this="" very=""> 100 GeV) by the High Energy Stereoscopic System (H.E.S.S.) from observations between September 2009 and December 2011 for a total live time of 34.9 h. Gamma rays above 200 GeV are detected at a significance of 9.4σ. A hint of variability at the 2.5σ level is found. An integral flux I(E > 200 GeV) = (3.3 ± 1.1 ± 0.7) × 10 ph cm s and a photon index Γ = 4.6 ± 0.7 ± 0.2 are measured. Multi-wavelength light curves in HE, X-ray and optical bands show strong variability, and a minimal variability timescale of eight days is estimated from the optical light curve. A single-zone leptonic synchrotron self-Compton scenario satisfactorily reproduces the multi-wavelength data. In this model, the emitting region is out of equipartition and the jet is particle dominated. Because of its high redshift compared to other sources observed at TeV energies, the very high energy emission from PKS 0301-243 is attenuated by the extragalactic background light (EBL) and the measured spectrum is used to derive an upper limit on the opacity of the EBL. © 2013 ESO.</e>
Keywords: BL Lacertae objects: general; BL Lacertae objects: individual: PKS 0301-243; Galaxies: active; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Discovery of VHE γ-ray emission and multi-wavelength observations of the BL Lacertae object 1RXS J101015.9-311909 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Astronomy & Astrophysics, 2012)
Keywords: gamma rays: galaxies; galaxies: active; BL Lacertae objects: individual: 1RXS J101015.9-311909

Discovery of VHE emission towards the Carina arm region with the H.E.S.S. telescope array: HESS? J1018-589 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Astronomy & Astrophysics, 2012)
The Carina arm region, containing the supernova remnant SNR? G284.3-1.8, the high-energy (HE; E > 100 MeV) binary 1FGL? J1018.6-5856 and the energetic pulsar PSR? J1016-5857 and its nebula, has been observed with the H.E.S.S. telescope array. The observational coverage of the region in very-high-energy (VHE; E > 0.1? TeV) γ-rays benefits from deep exposure (40? h) of the neighboring open cluster Westerlund 2. The observations have revealed a new extended region of VHE γ-ray emission. The new VHE source HESS? J1018-589 shows a bright, point-like emission region positionally coincident with SNR? G284.3-1.8 and 1FGL? J1018.6-5856 and a diffuse extension towards the direction of PSR? J1016-5857. A soft (Γ = 2.7 ± 0.5) photon? index, with a differential flux at 1? TeV of N = (4.2 ± 1.1) × 10? TeV? cm? s is found for the point-like source, whereas the total emission region including the diffuse emission region is well fit by a power-law function with spectral index Γ = 2.9 ± 0.4 and differential flux at 1? TeV of N = (6.8 ± 1.6) × 10? TeV? cm? s. This H.E.S.S. detection motivated follow-up X-ray observations with the XMM-Newton satellite to investigate the origin of the VHE emission. The analysis of the XMM-Newton data resulted in the discovery of a bright, non-thermal point-like source (XMMU J101855.4-58564) with a photon index of Γ = 1.65 ± 0.08 in the center of SNR? G284.3-1.8, and a thermal, extended emission region coincident with its bright northern filament. The characteristics of this thermal emission are used to estimate the plasma density in the region as n 0.5 cm (2.9? kpc/d). The position of XMMU? J101855.4-58564 is compatible with the position reported by the Fermi-LAT collaboration for the binary system 1FGL? J1018.6-5856 and the variable Swift XRT source identified with it. The new X-ray data are used alongside archival multi-wavelength data to investigate the relationship between the VHE γ-ray emission from HESS? J1018-589 and the various potential counterparts in the Carina arm region. © ESO, 2012.
Keywords: Gamma rays: stars; ISM: individual objects: 1FGL J1018.6-5856; ISM: individual objects: PSRJ1016-5857; ISM: individual objects: SNRG284.3-1.8

Erratum: H.E.S.S. detection of TeV emission from the interaction region between the supernova remnant G349.7+0.2 and a molecular cloud (Astronomy and Astrophysics (2015)) - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astronomy & Astrophysics, 2015)
Keywords: Errata; addenda; Gamma rays: general; ISM: clouds; ISM: supernova remnants

Erratum: "Search for Dark Matter Annihilation Signals from the Fornax Galaxy Cluster with H.E.S.S.'' (2012, ApJ, 750, 123) - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Barres De Almeida, U.; Becherini, Y.; Becker, J.; Behera, B.; Bernlöhr, K.; et al. (Astrophysical Journal, 2014)

Erratum to HESS J1640-465 - an exceptionally luminous TeV γ -ray supernova remnant - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
Keywords: Addenda; Errata; ISM: individual objects: G338.3-0.0; ISM: supernova remnants; Radiation mechanisms: non-thermal

Flux upper limits for 47 AGN observed with H.E.S.S. in 2004 - 2011 - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
Context. About 40% of the observation time of the High Energy Stereoscopic System (H.E.S.S.) is dedicated to studying active galactic nuclei (AGN), with the aim of increasing the sample of known extragalactic very-high-energy (VHE, E > 100 GeV) sources and constraining the physical processes at play in potential emitters. Aims. H.E.S.S. observations of AGN, spanning a period from April 2004 to December 2011, are investigated to constrain their γ-ray fluxes. Only the 47 sources without significant excess detected at the position of the targets are presented. Methods. Upper limits on VHE fluxes of the targets were computed and a search for variability was performed on the nightly time scale. Results. For 41 objects, the flux upper limits we derived are the most constraining reported to date. These constraints at VHE are compared with the flux level expected from extrapolations of Fermi-LAT measurements in the two-year catalog of AGN. The H.E.S.S. upper limits are at least a factor of two lower than the extrapolated Fermi-LAT fluxes for 11 objects. Taking into account the attenuation by the extragalactic background light reduces the tension for all but two of them, suggesting intrinsic curvature in the high-energy spectra of these two AGN. Conclusions. Compilation efforts led by current VHE instruments are of critical importance for target-selection strategies before the advent of the Cherenkov Telescope Array (CTA). © ESO, 2014.
Keywords: Galaxies: active; Gamma rays: galaxies

HESS and Fermi-LAT discovery of γ-rays from the blazar 1ES 1312-423 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2013)
A deep observation campaign carried out by the High Energy Stereoscopic System (HESS) on Centaurus A enabled the discovery of γ-rays from the blazar 1ES 1312-423, 2° away from the radio galaxy. With a differential flux at 1 TeV of f(1 TeV) = (1.9 ± 0.6 ± 0.4) × 10 cm s TeV corresponding to 0.5 per cent of the Crab nebula differential flux and a spectral index γ = 2.9 ± 0.5 ± 0.2, 1ES 1312-423 is one of the faintest sources ever detected in the very high energy (E <100 GeV) extragalactic sky. A careful analysis using three and a half years of Fermi Large Area Telescope (Fermi-LAT) data allows the discovery at high energies (100 < E MeV) of a hard spectrum (γ =1.4±0.4stat ±0.2sys) source coincident with 1ES 1312-423. Radio, optical, UV and X-ray observations complete the spectral energy distribution of this blazar, now covering 16 decades in energy. The emission is successfully fitted with a synchrotron self-Compton model for the non-thermal component, combined with a blackbody spectrum for the optical emission from the host galaxy. © 2013 The Authors. Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Bl Lacertae objects: individual: 1ES 1312-423; Galaxies: active; Galaxies: jets; Gamma-rays: galaxies.; Radiation mechanisms: non-thermal

H.E.S.S. detection of TeV emission from the interaction region between the supernova remnant G349.7+0.2 and a molecular cloud - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguner, E. O.; Backes, Michael; Balenderans, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astronomy & Astrophysics, 2015)
G349.7+0.2 is a young Galactic supernova remnant (SNR) located at the distance of 11.5 kpc and observed across the entire electromagnetic spectrum from radio to high energy (HE; 0.1 GeV < E < 100 GeV) γ-rays. Radio and infrared observations indicate that the remnant is interacting with a molecular cloud. In this paper, the detection of very high energy (VHE, E > 100 GeV) γ-ray emission coincident with this SNR with the High Energy Stereoscopic System (H.E.S.S.) is reported. This makes it one of the farthest Galactic SNR ever detected in this domain. An integral flux F (E > 400 GeV) = (6.5 ± 1.1 ± 1.3) × 10 ph cm s corresponding to ∼0.7% of that of the Crab Nebula and to a luminosity of ∼10 erg s above the same energy threshold, and a steep photon index Γ = 2.8 ± 0.27stat ± 0.20 are measured. The analysis of more than 5 yr of Fermi-LAT data towards this source shows a power-law like spectrum with a best-fit photon index Γ = 2.2 ± 0.04 . The combined γ-ray spectrum of G349.7+0.2 can be described by either a broken power-law (BPL) or a power-law with exponential (or sub-exponential) cutoff(PLC). In the former case, the photon break energy is found at E = 55 GeV, slightly higher than what is usually observed in the HE/VHE γ-ray emitting middle-aged SNRs known to be interacting with molecular clouds. In the latter case, the exponential (respectively sub-exponential) cutoff energy is measured at E = 1.4 (respectively 0.35 ) TeV. A pion-decay process resulting from the interaction of the accelerated protons and nuclei with the dense surrounding medium is clearly the preferred scenario to explain the γ-ray emission. The BPL with a spectral steepening of 0.5-1 and the PLC provide equally good fits to the data. The product of the average gas density and the total energy content of accelerated protons and nuclei amounts to n W ∼ 5 × 10 erg cm.
Keywords: Gamma rays: General; ISM: clouds; ISM: supernova remnants

H.E.S.S. discovery of VHE γ-rays from the quasar PKS 1510-089 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Behera, B.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2013)
The quasar PKS 1510-089 (z = 0.361) was observed with the H.E.S.S. array of imaging atmospheric Cherenkov telescopes during high states in the optical and GeV bands, to search for very high energy (VHE, defined as E ≥ 0.1 TeV) emission. VHE γ-rays were detected with a statistical significance of 9.2 standard deviations in 15.8 h of H.E.S.S. data taken during March and April 2009. A VHE integral flux of I(0.15 TeV < E < 1.0TeV) = (1.0 ±0.2 ±0.2) ×10 cm s is measured. The best-fit power law to the VHE data has a photon index of γ = 5.4 ± 0.7 ± 0.3. The GeV and optical light curves show pronounced variability during the period of H.E.S.S. observations. However, there is insufficient evidence to claim statistically significant variability in the VHE data. Because of its relatively high redshift, the VHE flux from PKS 1510-089 should suffer considerable attenuation in the intergalactic space due to the extragalactic background light (EBL). Hence, the measured γ-ray spectrum is used to derive upper limits on the opacity due to EBL, which are found to be comparable with the previously derived limits from relatively-nearby BL Lac objects. Unlike typical VHE-detected blazars where the broadband spectrum is dominated by nonthermal radiation at all wavelengths, the quasar PKS 1510-089 has a bright thermal component in the optical to UV frequency band. Among all VHE detected blazars, PKS 1510-089 has the most luminous broad line region. The detection of VHE emission from this quasar indicates a low level of γ - γ absorption on the internal optical to UV photon field. © 2013 ESO.
Keywords: Gamma rays: galaxies; Infrared: diffuse background; Quasars: individual: PKS 1510; 089

HESS J1640-465-an exceptionally luminous TeV γ-ray supernova remnant - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
The results of follow-up observations of the TeV γ-ray source HESS J1640-465 from 2004 to 2011 with the High Energy Stereoscopic System (HESS) are reported in this work. The spectrum is well described by an exponential cut-offpower law with photon index γ = 2.11 ± 0.09 ± 0.10, and a cut-offenergy of E = 6.0 TeV. The TeV emission is significantly extended and overlaps with the northwestern part of the shell of the SNR G338.3-0.0. The new HESS results, a re-analysis of archival XMM-Newton data and multiwavelength observations suggest that a significant part of the γ-ray emission from HESS J1640-465 originates in the supernova remnant shell. In a hadronic scenario, as suggested by the smooth connection of the GeV and TeV spectra, the product of total proton energy and mean target density could be as high as W 4 × 10(d/10kpc) erg cm. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: G338.3-0.0-ISM; Individual objects; Non-thermal-ISM; Radiation mechanisms; Supernova remnants

HESS J1818-154, a new composite supernova remnant discovered in TeV gamma rays and X-rays - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
Composite supernova remnants (SNRs) constitute a small subclass of the remnants of massive stellar explosions where non-thermal radiation is observed from both the expanding shell-like shock front and from a pulsar wind nebula (PWN) located inside of the SNR. These systems represent a unique evolutionary phase of SNRs where observations in the radio, X-ray, and γ-ray regimes allow the study of the co-evolution of both these energetic phenomena. In this article, we report results from observations of the shell-type SNR G 15.4+0.1 performed with the High Energy Stereoscopic System (H.E.S.S.) and XMM-Newton. A compact TeV γ-ray source, HESS J1818-154, located in the center and contained within the shell of G 15.4+0.1 is detected by H.E.S.S. and featurs a spectrum best represented by a power-law model with a spectral index of-2.3 ± 0.3 ± 0.2 and an integral flux of F(> 0.42 TeV) = (0.9 ± 0.3 ± 0.2) × 10 cm s. Furthermore, a recent observation with XMM-Newton reveals extended X-ray emission strongly peaked in the center of G 15.4+0.1. The X-ray source shows indications of an energy-dependent morphology featuring a compact core at energies above 4 keV and more extended emission that fills the entire region within the SNR at lower energies. Together, the X-ray and VHE γ-ray emission provide strong evidence of a PWN located inside the shell of G 15.4+0.1 and this SNR can therefore be classified as a composite based on these observations. The radio, X-ray, and γ-ray emission from the PWN is compatible with a one-zone leptonic model that requires a low average magnetic field inside the emission region. An unambiguous counterpart to the putative pulsar, which is thought to power the PWN, has been detected neither in radio nor in X-ray observations of G 15.4+0.1. © 2014 ESO.
Keywords: Gamma rays: general; Methods: observational; Supernovae: individual: HESS J1818-154; X-rays: general; X-rays: individuals: G15.4+0.1

HESS J1943+213: A candidate extreme BL Lacertae object - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; et al. (Astronomy & Astrophysics, 2011)
Context. The H.E.S.S. Cherenkov telescope array has been surveying the Galactic plane for new VHE (>100 GeV) gamma-ray sources. Aims. We report on a newly detected point-like source, HESS J1943+213. This source coincides with an unidentified hard X-ray source IGR J19443+2117, which was proposed to have radio and infrared counterparts. Methods. We combine new H.E.S.S., Fermi/LAT and Nançay Radio Telescope observations with pre-existing non-simultaneous multi-wavelength observations of IGR J19443+2117 and discuss the likely source associations as well as the interpretation as an active galactic nucleus, a gamma-ray binary or a pulsar wind nebula. Results. HESS J1943+213 is detected at the significance level of 7.9σ (post-trials) at RA(J2000)= 19 4355 ± 1 ± 1 , Dec(J2000)= +21° 18'8" ± 17" ± 20". The source has a soft spectrum with photon index Γ = 3.1 ± 0.3 ± 0.2 and a flux above 470 GeV of (1.3 ± 0.2 ± 0.3) × 10 cm s . There is no Fermi/LAT counterpart down to a flux limit of 6 × 10 cm s in the 0.1-100 GeV energy range (95% confidence upper limit calculated for an assumed power-law model with a photon index Γ = 2.0). The data from radio to VHE gamma-rays do not show any significant variability. Conclusions. The lack of a massive stellar counterpart disfavors the binary hypothesis, while the soft VHE spectrum would be very unusual in case of a pulsar wind nebula. In addition, the distance estimates for Galactic counterparts places them outside of the Milky Way. All available observations favor an interpretation as an extreme, high-frequency peaked BL Lac object with a redshift z > 0.14. This would be the first time a blazar is detected serendipitously from ground-based VHE observations, and the first VHE AGN detected in the Galactic Plane. © 2011 ESO.
Keywords: BL Lacertae objects: individual: IGR J19443+2117; galaxies: active; gamma rays: general

H.E.S.S. observations of the binary system PSR B1259-63/LS 2883 around the 2010/2011 periastron passage - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Aims. We present very high energy (VHE; E > 100 GeV) data from the γ-ray binary system PSR B1259-63/LS 2883 taken around its periastron passage on 15th of December 2010 with the High Energy Stereoscopic System (H.E.S.S.) of Cherenkov Telescopes. We aim to search for a possible TeV counterpart of the GeV flare detected by the Fermi LAT. In addition, we aim to study the current periastron passage in the context of previous observations taken at similar orbital phases, testing the repetitive behaviour of the source. Methods. Observations at VHEs were conducted with H.E.S.S. from 9th to 16th of January 2011. The total dataset amounts to 6 h of observing time. The data taken around the 2004 periastron passage were also re-analysed with the current analysis techniques in order to extend the energy spectrum above 3 TeV to fully compare observation results from 2004 and 2011. Results. The source is detected in the 2011 data at a significance level of 11.5σ revealing an averaged integral flux above 1 TeV of (1.01 ± 0.18 ± 0.20) × 10 cm s. The differential energy spectrum follows a power-law shape with a spectral index Γ = 2.92 ± 0.30 ± 0.20 and a flux normalisation at 1 TeV of N = (1.95 ± 0.32 ± 0.39) × 10 TeV cm s. The measured light curve does not show any evidence for variability of the source on the daily scale. The re-analysis of the 2004 data yields results compatible with the published ones. The differential energy spectrum measured up to 10 TeV is consistent with a power law with a spectral index Γ = 2.81 ± 0.10 ± 0.20 and a flux normalisation at 1 TeV of N = (1.29 ± 0.08 ± 0.26) × 10 TeV cm s. Conclusions. The measured integral flux and the spectral shape of the 2011 data are compatible with the results obtained around previous periastron passages. The absence of variability in the H.E.S.S. data indicates that the GeV flare observed by Fermi LAT in the time period covered also by H.E.S.S. observations originates in a different physical scenario than the TeV emission. Moreover, the comparison of the new results to the results from the 2004 observations made at a similar orbital phase provides a stronger evidence of the repetitive behaviour of the source. © ESO, 2013.
Keywords: Gamma rays: general; Pulsars: individual: PSR B1259-63; Stars: individual: LS 2883; X-rays: binaries

HESS observations of the Carina nebula and its enigmatic colliding wind binary Eta Carinae - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
The massive binary system Eta Carinae and the surrounding Hii complex, the Carina nebula, are potential particle acceleration sites from which very high energy (VHE; E≥ 100GeV) γ-ray emission could be expected. This paper presents data collected during VHE γ-ray observations with the HESS telescope array from 2004 to 2010, which cover a full orbit of Eta Carinae. In the 33.1-h data set no hint of significant γ-ray emission from Eta Carinae has been found and an upper limit on the γ-ray flux of (99per cent confidence level) is derived above the energy threshold of 470GeV. Together with the detection of high energy (HE; 0.1 ≤E≤ 100GeV) γ-ray emission by the Fermi Large Area Telescope up to 100GeV, and assuming a continuation of the average HE spectral index into the VHE domain, these results imply a cut-off in the γ-ray spectrum between the HE and VHE γ-ray range. This could be caused either by a cut-off in the accelerated particle distribution or by severe γ-γ absorption losses in the wind collision region. Furthermore, the search for extended γ-ray emission from the Carina nebula resulted in an upper limit on the γ-ray flux of (99per cent confidence level). The derived upper limit of ∼23 on the cosmic ray enhancement factor is compared with results found for the old-age mixed-morphology supernova remnant W28. © 2012 The Authors Monthly Notices of the Royal Astronomical Society © 2012 RAS.
Keywords: Acceleration of particles; ISM: individual objects: Carina nebula; ISM: individual objects: Eta Carina; Open clusters and associations: general; Radiation mechanisms: non-thermal; X-rays: binaries

H.E.S.S. observations of the Crab during its March 2013 GeV gamma-ray flare - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
Context. On March 4, 2013 the Fermi-LAT and AGILE reported a flare from the direction of the Crab nebula in which the high-energy (HE; E > 100 MeV) flux was six times above its quiescent level. Simultaneous observations in other energy bands give us hints about the emission processes during the flare episode and the physics of pulsar wind nebulae in general. Aims. We search for variability in the emission of the Crab nebula at very-high energies (VHE; E > 100 GeV), using contemporaneous data taken with the H.E.S.S. array of Cherenkov telescopes. Methods. Observational data taken with the H.E.S.S. instrument on five consecutive days during the flare were analysed for the flux and spectral shape of the emission from the Crab nebula. Night-wise light curves are presented with energy thresholds of 1 TeV and 5 TeV. Results. The observations conducted with H.E.S.S. on March 6 to March 10, 2013 show no significant changes in the flux. They limit the variation in the integral flux above 1 TeV to less than 63% and the integral flux above 5 TeV to less than 78% at a 95% confidence level. © 2014 ESO.
Keywords: Gamma rays: ISM; ISM: individual objects: Crab nebula; Radiation mechanisms: non-thermal; Relativistic processes

H.E.S.S. observations of the globular clusters NGC 6388 and M15 and search for a dark matter signal - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; et al. (Astrophysical Journal, 2011)
Observations of the globular clusters (GCs) NGC 6388 and M15 were carried out by the High Energy Stereoscopic System array of Cherenkov telescopes for a live time of 27.2 and 15.2 hr, respectively. No gamma-ray signal is found at the nominal target position of NGC 6388 and M15. In the primordial formation scenario, GCs are formed in a dark matter (DM) halo and DM could still be present in the baryon-dominated environment of GCs. This opens the possibility of observing a DM self-annihilation signal. The DM content of the GCs NGC 6388 and M15 is modeled taking into account the astrophysical processes that can be expected to influence the DM distribution during the evolution of the GC: the adiabatic contraction of DM by baryons, the adiabatic growth of a black hole in the DM halo, and the kinetic heating of DM by stars. Ninety-five percent confidence level exclusion limits on the DM particle velocity-weighted annihilation cross section are derived for these DM halos. In the TeV range, the limits on the velocity-weighted annihilation cross section are derived at the 10 cm s level and a few 10 cm s for NGC 6388 and M15, respectively. © 2011. The American Astronomical Society. All rights reserved..
Keywords: black hole physics; dark matter; gamma rays: general; globular clusters: individual (NGC 6388; M15)

H.E.S.S. reveals a lack of TeV emission from the supernova remnant Puppis A - Abramowski, A.; Aharonian, F.; Ait Benkhali, F.; Akhperjanian, A. G.; Angüner, E. O.; Backes, M.; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Becker Tjus, J.; Berge, D.; et al. (Astronomy & Astrophysics, 2015)
Results. The analysis of the H.E.S.S. data does not reveal any significant emission towards Puppis A. The derived upper limits on the differential photon flux imply that its broadband γ-ray spectrum must exhibit a spectral break or cutoff. By combining Fermi-LAT and H.E.S.S. measurements, the 99% confidence-level upper limits on such a cutoff are found to be 450 and 280 GeV, assuming a power law with a simple exponential and a sub-exponential cutoff, respectively. It is concluded that none of the standard limitations (age, size, radiative losses) on the particle acceleration mechanism, assumed to be continuing at present, can explain the lack of VHE signal. The scenario in which particle acceleration has ceased some time ago is considered as an alternative explanation. The HE/VHE spectrum of Puppis A could then exhibit a break of non-radiative origin (as observed in several other interacting SNRs, albeit at somewhat higher energies), owing to the interaction with dense and neutral material, in particular towards the NE region.
Keywords: Acceleration of particles; Cosmic rays; Gamma rays: ISM; ISM: individual objects: Puppis A; Radiation mechanisms: non-thermal

Identification of HESS J1303-631 as a pulsar wind nebula through γ -ray, X-ray, and radio observations - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
Aims. The previously unidentified very high-energy (VHE; E > 100 GeV) γ-ray source HESS J1303-631, discovered in 2004, is re-examined including new data from the H.E.S.S. Cherenkov telescope array in order to identify this object. Archival data from the XMM-Newton X-ray satellite and from the PMN radio survey are also examined. Methods. Detailed morphological and spectral studies of VHE γ-ray emission as well as of the XMM-Newton X-ray data are performed. Radio data from the PMN survey are used as well to construct a leptonic model of the source. The γ-ray and X-ray spectra and radio upper limit are used to construct a one zone leptonic model of the spectral energy distribution (SED). Results. Significant energy-dependent morphology of the γ-ray source is detected with high-energy emission (E > 10 TeV) positionally coincident with the pulsar PSR J1301-6305 and lower energy emission (E < 2 TeV) extending ∼0.4° to the southeast of the pulsar. The spectrum of the VHE source can be described with a power-law with an exponential cut-off N = (5.6 ± 0.5) × 10 ± TeV ± cm ± s, Γ = 1.5 ± 0.2) and E = (7.7 ± ± ± 2.2) TeV. The pulsar wind nebula (PWN) is also detected in X-rays, extending ∼2-3′ from the pulsar position towards the center of the γ-ray emission region. A potential radio counterpart from the PMN survey is also discussed, showing a hint for a counterpart at the edge of the X-ray PWN trail and is taken as an upper limit in the SED. The extended X-ray PWN has an unabsorbed flux of F ∼ 1.6 × 10 erg cm and is detected at a significance of 6.5σ. The SED is well described by a one zone leptonic scenario which, with its associated caveats, predicts a very low average magnetic field for this source. Conclusions. Significant energy-dependent morphology of this source, as well as the identification of an associated X-ray PWN from XMM-Newton observations enable identification of the VHE source as an evolved PWN associated to the pulsar PSR J1301-6305. This identification is supported by the one zone leptonic model, which suggests that the energetics of the γ-ray and X-ray radiation are such that they may have a similar origin in the pulsar nebula. However, the large discrepancy in emission region sizes and the low level of synchrotron radiation suggest a multi-population leptonic nature. The low implied magnetic field suggests that the PWN has undergone significant expansion. This would explain the low level of synchrotron radiation and the difficulty in detecting counterparts at lower energies, the reason this source was originally classified as a "dark" VHE γ-ray source. © ESO, 2012.
Keywords: Gamma rays: general; ISM: individual objects: HESS J1303-631; Pulsars: individual: PSR J1301-6305

Long-term monitoring of PKS 2155-304 with ATOM and H.E.S.S.: Investigation of optical/γ-ray correlations in different spectral states - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguner, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astronomy & Astrophysics, 2014)
In this paper we report on the analysis of all the available optical and very high-energy γ-ray (>200 GeV) data for the BL Lac object PKS 2155-304, collected simultaneously with the ATOM and H.E.S.S. telescopes from 2007 until 2009. This study also includes X-ray (RXTE, Swift) and high-energy γ-ray (Fermi-LAT) data. During the period analysed, the source was transitioning from its flaring to quiescent optical states, and was characterized by only moderate flux changes at different wavelengths on the timescales of days and months. A flattening of the optical continuum with an increasing optical flux can be noted in the collected dataset, but only occasionally and only at higher flux levels. We did not find any universal relation between the very high-energy γ-ray and optical flux changes on the timescales from days and weeks up to several years. On the other hand, we noted that at higher flux levels the source can follow two distinct tracks in the optical flux-colour diagrams, which seem to be related to distinct γ-ray states of the blazar. The obtained results therefore indicate a complex scaling between the optical and γ-ray emission of PKS 2155-304, with different correlation patterns holding at different epochs, and a γ-ray flux depending on the combination of an optical flux and colour rather than a flux alone.
Keywords: BL Lacertae objects: individual: PKS 2155-304; Black hole physics; Galaxies: active; Galaxies: jets; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Long-term TeV and X-ray observations of the gamma-ray binary hess j0632+057 - Aliu, E.; Archambault, S.; Aune, T.; Behera, B.; Beilicke, M.; Benbow, W.; Berger, K.; Bird, Ralph; Bouvier, A.; Buckley, J. H.; Bugaev, V.; Byrum, K.; et al. (Astrophysical Journal, 2014)
HESS J0632+057 is the only gamma-ray binary known so far whose position in the sky allows observations with ground-based observatories in both the northern and southern hemispheres. Here we report on long-term observations of HESS J0632+057 conducted with the Very Energetic Radiation Imaging Telescope Array System and High Energy Stereoscopic System Cherenkov telescopes and the X-ray satellite Swift, spanning a time range from 2004 to 2012 and covering most of the system's orbit. The very-high-energy (VHE) emission is found to be variable and is correlated with that at X-ray energies. An orbital period of days is derived from the X-ray data set, which is compatible with previous results, P = (321 ± 5) days. The VHE light curve shows a distinct maximum at orbital phases close to 0.3, or about 100 days after periastron passage, which coincides with the periodic enhancement of the X-ray emission. Furthermore, the analysis of the TeV data shows for the first time a statistically significant (>6.5σ) detection at orbital phases 0.6-0.9. The obtained gamma-ray and X-ray light curves and the correlation of the source emission at these two energy bands are discussed in the context of the recent ephemeris obtained for the system. Our results are compared to those reported for other gamma-ray binaries. © 2014. The American Astronomical Society. All rights reserved..
Keywords: acceleration of particles; binaries:general

Measurement of the extragalactic background light imprint on the spectra of the brightest blazars observed with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
The extragalactic background light (EBL) is the diffuse radiation with the second highest energy density in the Universe after the cosmic microwave background. The aim of this study is the measurement of the imprint of the EBL opacity to γ-rays on the spectra of the brightest extragalactic sources detected with the High Energy Stereoscopic System (H.E.S.S.). The originality of the method lies in the joint fit of the EBL optical depth and of the intrinsic spectra of the sources, assuming intrinsic smoothness. Analysis of a total of ∼10γ-ray events enables the detection of an EBL signature at the 8.8σ level and constitutes the first measurement of the EBL optical depth using very-high energy (E > 100 GeV) γ-rays. The EBL flux density is constrained over almost two decades of wavelengths [0.30 μm, 17 μm] and the peak value at 1.4 μm is derived as λF = 15 ± 2 ± 3 nW m sr. © 2013 ESO.
Keywords: BL Lacertae objects: general; Cosmic background radiation; Gamma rays: galaxies

Probing the gamma-ray emission from HESS J1834-087 using H.E.S.S. and Fermi LAT observations - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2015)
Aims. Previous observations with the High Energy Stereoscopic System (H.E.S.S.) have revealed an extended very-high-energy (VHE; E > 100 GeV) γ-ray source, HESS J1834-087, coincident with the supernova remnant (SNR)W41. The origin of the γ-ray emission was investigated in more detail with the H.E.S.S. array and the Large Area Telescope (LAT) onboard the Fermi Gamma-ray Space Telescope. Methods. The γ-ray data provided by 61 h of observations with H.E.S.S., and four years with the Fermi LAT were analyzed, covering over five decades in energy from 1.8 GeV up to 30 TeV. The morphology and spectrum of the TeV and GeV sources were studied and multiwavelength data were used to investigate the origin of the γ-ray emission toward W41. Results. The TeV source can be modeled with a sum of two components: one point-like and one significantly extended (σ = 0.17° ± 0. 01°), both centered on SNR W41 and exhibiting spectra described by a power law with index Γ ≃ 2.6. The GeV source detected with Fermi LAT is extended (σ = 0.15° ± 0.03°) and morphologically matches the VHE emission. Its spectrum can be described by a power-law model with an index Γ = 2.15 ± 0.12 and smoothly joins the spectrum of the whole TeV source. A break appears in the γ-ray spectra around 100 GeV. No pulsations were found in the GeV range. Conclusions. Two main scenarios are proposed to explain the observed emission: a pulsar wind nebula (PWN) or the interaction of SNRW41 with an associated molecular cloud. X-ray observations suggest the presence of a point-like source (a pulsar candidate) near the center of the remnant and nonthermal X-ray di ffuse emission that could arise from the possibly associated PWN. The PWN scenario is supported by the compatible positions of the TeV and GeV sources with the putative pulsar. However, the spectral energy distribution from radio to γ-rays is reproduced by a one-zone leptonic model only if an excess of low-energy electrons is injected following a Maxwellian distribution by a pulsar with a high spin-down power (>10 ergs). This additional low-energy component is not needed if we consider that the point-like TeV source is unrelated to the extended GeV and TeV sources. The interacting SNR scenario is supported by the spatial coincidence between the γ-ray sources, the detection of OH (1720 MHz) maser lines, and the hadronic modeling.
Keywords: Acceleration of particles; Cosmic rays; Ism: Clouds; Ism: Supernova remnants

Search for dark matter annihilation signals from the Fornax galaxy cluster with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Astrophysical Journal, 2012)
The Fornax galaxy cluster was observed with the High Energy Stereoscopic System for a total live time of 14.5hr, searching for very high energy (VHE; E > 100GeV) γ-rays from dark matter (DM) annihilation. No significant signal was found in searches for point-like and extended emissions. Using several models of the DM density distribution, upper limits on the DM velocity-weighted annihilation cross-section 〈σv〉 as a function of the DM particle mass are derived. Constraints are derived for different DM particle models, such as those arising from Kaluza-Klein and supersymmetric models. Various annihilation final states are considered. Possible enhancements of the DM annihilation γ-ray flux, due to DM substructures of the DM host halo, or from the Sommerfeld effect, are studied. Additional γ-ray contributions from internal bremsstrahlung and inverse Compton radiation are also discussed. For a DM particle mass of 1TeV, the exclusion limits at 95% of confidence level reach values of 〈σv〉 10 cm s, depending on the DM particle model and halo properties. Additional contribution from DM substructures can improve the upper limits on 〈σv〉 by more than two orders of magnitude. At masses around 4.5TeV, the enhancement by substructures and the Sommerfeld resonance effect results in a velocity-weighted annihilation cross-section upper limit at the level of 〈σv〉 10 cm s. © 2012. The American Astronomical Society. All rights reserved.

Search for dark matter annihilation signatures in H.E.S.S. observations of dwarf spheroidal galaxies - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2014)
Dwarf spheroidal galaxies of the Local Group are close satellites of the Milky Way characterized by a large mass-to-light ratio and are not expected to be the site of nonthermal high-energy gamma-ray emission or intense star formation. Therefore they are among the most promising candidates for indirect dark matter searches. During the last years the High Energy Stereoscopic System (H.E.S.S.) of imaging atmospheric Cherenkov telescopes observed five of these dwarf galaxies for more than 140 hours in total, searching for TeV gamma-ray emission from annihilation of dark matter particles. The new results of the deep exposure of the Sagittarius dwarf spheroidal galaxy, the first observations of the Coma Berenices and Fornax dwarves and the reanalysis of two more dwarf spheroidal galaxies already published by the H.E.S.S. Collaboration, Carina and Sculptor, are presented. In the absence of a significant signal new constraints on the annihilation cross section applicable to weakly interacting massive particles (WIMPs) are derived by combining the observations of the five dwarf galaxies. The combined exclusion limit depends on the WIMP mass and the best constraint is reached at 1-2 TeV masses with a cross-section upper bound of ∼3.9×10-24cm3s-1 at a 95% confidence level.

Search for extended γ-ray emission around AGN with H.E.S.S. and Fermi -LAT - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2014)
Context. Very-high-energy (VHE; E > 100 GeV) γ-ray emission from blazars inevitably gives rise to electron-positron pair production through the interaction of these γ-rays with the extragalactic background light (EBL). Depending on the magnetic fields in the proximity of the source, the cascade initiated from pair production can result in either an isotropic halo around an initially beamed source or a magnetically broadened cascade flux. Aims. Both extended pair-halo (PH) and magnetically broadened cascade (MBC) emission from regions surrounding the blazars 1ES 1101-232, 1ES 0229+200, and PKS 2155-304 were searched for using VHE γ-ray data taken with the High Energy Stereoscopic System (H.E.S.S.) and high-energy (HE; 100 MeV < E < 100 GeV) γ-ray data with the Fermi Large Area Telescope (LAT). Methods. By comparing the angular distributions of the reconstructed γ-ray events to the angular profiles calculated from detailed theoretical models, the presence of PH and MBC was investigated. Results. Upper limits on the extended emission around 1ES 1101-232, 1ES 0229+200, and PKS 2155-304 are found to be at a level of a few per cent of the Crab nebula flux above 1 TeV, depending on the assumed photon index of the cascade emission. Assuming strong extra-Galactic magnetic field (EGMF) values, >10 G, this limits the production of pair haloes developing from electromagnetic cascades. For weaker magnetic fields, in which electromagnetic cascades would result in MBCs, EGMF strengths in the range (0.3-3) × 10 G were excluded for PKS 2155-304 at the 99% confidence level, under the assumption of a 1 Mpc coherence length. © ESO, 2014.
Keywords: BL Lacertae objects: individual: 1ES 0229+200; BL Lacertae objects: individual: 1ES 1101-232; BL Lacertae objects: individual: PKS 2155-304; Galaxies: magnetic fields; Gamma rays: galaxies; Intergalactic medium

Search for photon-linelike signatures from dark matter annihilations with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Physical Review Letters, 2013)
Gamma-ray line signatures can be expected in the very-high-energy (E >100 GeV) domain due to self-annihilation or decay of dark matter (DM) particles in space. Such a signal would be readily distinguishable from astrophysical γ-ray sources that in most cases produce continuous spectra that span over several orders of magnitude in energy. Using data collected with the H.E.S.S. γ-ray instrument, upper limits on linelike emission are obtained in the energy range between ∼500 GeV and ∼25 TeV for the central part of the Milky Way halo and for extragalactic observations, complementing recent limits obtained with the Fermi-LAT instrument at lower energies. No statistically significant signal could be found. For monochromatic γ-ray line emission, flux limits of (2×107- 2×105) m2 s1 sr1 and (1×108-2×106) m2 s1 sr1 are obtained for the central part of the Milky Way halo and extragalactic observations, respectively. For a DM particle mass of 1 TeV, limits on the velocity-averaged DM annihilation cross section âŸ̈σvâŸ© reach ∼1027 cm3 s 1, based on the Einasto parametrization of the Galactic DM halo density profile. © 2013 American Physical Society.

Search for TeV gamma-ray emission from GRB 100621A, an extremely bright GRB in X-rays, with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
The long gamma-ray burst (GRB) 100621A, at the time the brightest X-ray transient ever detected by Swift-XRT in the 0.3-10 keV range, has been observed with the H.E.S.S. imaging air Cherenkov telescope array, sensitive to gamma radiation in the very-high-energy (VHE, >100 GeV) regime. Due to its relatively small redshift of z 0.5, the favourable position in the southern sky and the relatively short follow-up time (<700 s after the satellite trigger) of the H.E.S.S. observations, this GRB could be within the sensitivity reach of the H.E.S.S. instrument. The analysis of the H.E.S.S. data shows no indication of emission and yields an integral flux upper limit above 380 GeV of 4.2 × 10 cm s (95% confidence level), assuming a simple Band function extension model. A comparison to a spectral-temporal model, normalised to the prompt flux at sub-MeV energies, constraints the existence of a temporally extended and strong additional hard power law, as has been observed in the other bright X-ray GRB 130427A. A comparison between the H.E.S.S. upper limit and the contemporaneous energy output in X-rays constrains the ratio between the X-ray and VHE gamma-ray fluxes to be greater than 0.4. This value is an important quantity for modelling the afterglow and can constrain leptonic emission scenarios, where leptons are responsible for the X-ray emission and might produce VHE gamma rays. © 2014 ESO.
Keywords: Gamma rays: general; Gamma rays: stars; Gamma-ray burst: individual: GRB 100621A; X-rays: stars

Search for very-high-energy γ-ray emission from Galactic globular clusters with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Context. Globular clusters (GCs) are established emitters of high-energy (HE, 100 MeV < E < 100 GeV) γ-ray radiation which could originate from the cumulative emission of the numerous millisecond pulsars (msPSRs) in the clusters' cores or from inverse Compton (IC) scattering of relativistic leptons accelerated in the GC environment. These stellar clusters could also constitute a new class of sources in the very-high-energy (VHE, E > 100 GeV) γ-ray regime, judging from the recent detection of a signal from the direction of Terzan 5 with the H.E.S.S. telescope array. Aims. To search for VHE γ-ray sources associated with other GCs, and to put constraints on leptonic emission models, we systematically analyzed the observations towards 15 GCs taken with the H.E.S.S. array of imaging atmospheric Cherenkov telescopes. Methods. We searched for point-like and extended VHE γ-ray emission from each GC in our sample and also performed a stacking analysis combining the data from all GCs to investigate the hypothesis of a population of faint emitters. Assuming IC emission as the origin of the VHE γ-ray signal from the direction of Terzan 5, we calculated the expected γ-ray flux from each of the 15 GCs, based on their number of millisecond pulsars, their optical brightness and the energy density of background photon fields. Results. We did not detect significant VHE γ-ray emission from any of the 15 GCs in either of the two analyses. Given the uncertainties related to the parameter determinations, the obtained flux upper limits allow to rule out the simple IC/msPSR scaling model for NGC 6388 and NGC 7078. The upper limits derived from the stacking analyses are factors between 2 and 50 below the flux predicted by the simple leptonic scaling model, depending on the assumed source extent and the dominant target photon fields. Therefore, Terzan 5 still remains exceptional among all GCs, as the VHE γ-ray emission either arises from extra-ordinarily efficient leptonic processes, or from a recent catastrophic event, or is even unrelated to the GC itself. © 2013 ESO.
Keywords: Gamma rays: general; Globular clusters: general; Pulsars: general; Radiation mechanisms: non-thermal

Spectral analysis and interpretation of the γ-ray emission from the starburst galaxy NGC253 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Astrophysical Journal, 2012)
Very high energy (VHE; E ≥ 100 GeV) and high-energy (HE; 100 MeV ≤ E ≤ 100 GeV) data from γ-ray observations performed with the H.E.S.S. telescope array and the Fermi-LAT instrument, respectively, are analyzed in order to investigate the non-thermal processes in the starburst galaxy NGC253. The VHE γ-ray data can be described by a power law in energy with differential photon index Γ = 2.14 ± 0.18 ± 0.30 and differential flux normalization at 1TeV of F = (9.6 ± 1.5(+ 5.7, -2.9)) × 10 TeV cm s. A power-law fit to the differential HE γ-ray spectrum reveals a photon index of Γ = 2.24 ± 0.14 ± 0.03 and an integral flux between 200MeV and 200GeV of F(0.2-200 GeV) = (4.9 ± 1.0 ± 0.3) × 10 cm s. No evidence for a spectral break or turnover is found over the dynamic range of both the LAT instrument and the H.E.S.S. experiment: a combined fit of a power law to the HE and VHE γ-ray data results in a differential photon index Γ = 2.34 ± 0.03 with a p-value of 30%. The γ-ray observations indicate that at least about 20% of the energy of the cosmic rays (CRs) capable of producing hadronic interactions is channeled into pion production. The smooth alignment between the spectra in the HE and VHE γ-ray domain suggests that the same transport processes dominate in the entire energy range. Advection is most likely responsible for charged particle removal from the starburst nucleus from GeV to multiple TeV energies. In a hadronic scenario for the γ-ray production, the single overall power-law spectrum observed would therefore correspond to the mean energy spectrum produced by the ensemble of CR sources in the starburst region. © 2012. The American Astronomical Society. All rights reserved.
Keywords: convection; diffusion; galaxies: individual (NGC 253); galaxies: starburst; gamma rays: galaxies; radiation mechanisms: non-thermal

TeV γ-ray observations of the young synchrotron-dominated SNRs G1.9+0.3 and G330.2+1.0 with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
The non-thermal nature of the X-ray emission from the shell-type supernova remnants (SNRs) G1.9+0.3 and G330.2+1.0 is an indication of intense particle acceleration in the shock fronts of both objects. This suggests that the SNRs are prime candidates for very-high-energy (VHE; E > 0.1 TeV) γ -ray observations. G1.9+0.3, recently established as the youngest known SNR in the Galaxy, also offers a unique opportunity to study the earliest stages of SNR evolution in the VHE domain. The purpose of this work is to probe the level of VHE γ -ray emission from both SNRs and use this to constrain their physical properties. Observations were conducted with the H.E.S.S. (High Energy Stereoscopic System) Cherenkov Telescope Array over a more than six-year period spanning 2004-2010. The obtained data have effective livetimes of 67 h for G1.9+0.3 and 16 h for G330.2+1.0. The data are analysed in the context of the multiwavelength observations currently available and in the framework of both leptonic and hadronic particle acceleration scenarios. No significant γ -ray signal from G1.9+0.3 or G330.2+1.0 was detected. Upper limits (99 per cent confidence level) to the TeV flux from G1.9+0.3 and G330.2+1.0 for the assumed spectral index Γ = 2.5 were set at 5.6 × 10 cm s above 0.26 TeV and 3.2 × 10 cm s above 0.38 TeV, respectively. In a one-zone leptonic scenario, these upper limits imply lower limits on the interior magnetic field to B ≳ 12 μG for G1.9+0.3 and to B ≳ 8 μG for G330.2+1.0. In a hadronic scenario, the low ambient densities and the large distances to the SNRs result in very low predicted fluxes, for which the H.E.S.S. upper limits are not constraining. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Gamma-rays: ISM; ISM: magnetic fields; ISM: supernova remnants; Radiation mechanisms: non-thermal

The 2012 flare of PG 1553+113 seen with H.E.S.S. and Fermi-lat - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, Anna; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astrophysical Journal, 2015)
Very high energy (VHE, E > 100 GeV) γ-ray flaring activity of the high-frequency peaked BL Lac object PG 1553+113 has been detected by the H.E.S.S. telescopes. The flux of the source increased by a factor of 3 during the nights of 2012 April 26 and 27 with respect to the archival measurements with a hint of intra-night variability. No counterpart of this event has been detected in the Fermi-Large Area Telescope data. This pattern is consistent with VHE γ-ray flaring being caused by the injection of ultrarelativistic particles, emitting γ-rays at the highest energies. The dataset offers a unique opportunity to constrain the redshift of this source at z = 0.49 ± 0.04 using a novel method based on Bayesian statistics. The indication of intra-night variability is used to introduce a novel method to probe for a possible Lorentz invariance violation (LIV), and to set limits on the energy scale at which Quantum Gravity (QG) effects causing LIV may arise. For the subluminal case, the derived limits are E,1 > 4.10 × 10 GeV and E,2 > 2.10 × 10 GeV for linear and quadratic LIV effects, respectively.
Keywords: BL Lacertae objects: individual (PG 1553+113); galaxies: active; galaxies: distances and redshifts; gamma-rays: galaxies

The exceptionally powerful TeV γ-ray emitters in the Large Magellanic Cloud - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, M.; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Becker-Tjus, J.; Berge, D.; et al. (Science, 2015)
The Large Magellanic Cloud, a satellite galaxy of the Milky Way, has been observed with the High Energy Stereoscopic System (H.E.S.S.) above an energy of 100 billion electron volts for a deep exposure of 210 hours. Three sources of different types were detected: the pulsar wind nebula of the most energetic pulsar known, N 157B; the radio-loud supernova remnant N 132D; and the largest nonthermal x-ray shell, the superbubble 30 Dor C. The unique object SN 1987A is, unexpectedly, not detected, which constrains the theoretical framework of particle acceleration in very young supernova remnants. These detections reveal the most energetic tip of a γ-ray source population in an external galaxy and provide via 30 Dor C the unambiguous detection of γ-ray emission from a superbubble.

The high-energy γ-ray emission of AP Librae - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2015)
The γ-ray spectrum of the low-frequency-peaked BL Lac (LBL) object AP Librae is studied, following the discovery of very-high-energy (VHE; E > 100 GeV) γ-ray emission up to the TeV range by the H.E.S.S. experiment. This makes AP Librae one of the few VHE emitters of the LBL type. The measured spectrum yields a flux of (8.8 ± 1.5stat ± 1.8sys) × 10-12 cm-2 s-1 above 130 GeV and a spectral index of Γ = 2.65 ± 0.19stat ± 0.20sys. This study also makes use of Fermi-LAT observations in the high energy (HE, E> 100 MeV) range, providing the longest continuous light curve (5 years) ever published on this source. The source underwent a flaring event between MJD 56 306-56 376 in the HE range, with a flux increase of a factor of 3.5 in the 14 day bin light curve and no significant variation in spectral shape with respect to the low-flux state. While the H.E.S.S. and (low state) Fermi-LAT fluxes are in good agreement where they overlap, a spectral curvature between the steep VHE spectrum and the Fermi-LAT spectrum is observed. The maximum of the γ-ray emission in the spectral energy distribution is located below the GeV energy range.
Keywords: BL Lacertae objects: individual: AP Librae; Galaxies: active; Gamma rays: galaxies